Fibrinolytic Interventions Targeting Coagulation in COVID-19: A Narrative Review - Hegde, Megha; Raj, Saurav; Tikadar, Dhananjay; Swamy, Agadi Hiremath Viswanatha; Nyamagoud, Sanatkumar Bharamu (Indian Journal of Pharmacy Practice)
Background: Coagulation abnormalities, particularly Venous Thromboembolism (VTE) and Vaccine-Induced Thrombotic Thrombocytopenia (VITT), have emerged as consequential complications associated with COVID-19, significantly impacting morbidity and mortality. Understanding these complications is vital for effective therapeutic interventions. This review aims to comprehensively analyse the mechanisms, risks, and therapeutic interventions for COVID-19-induced coagulopathy and vaccine-related thrombotic events, focusing on the potential use of fibrinolytics as a treatment strategy. Materials and Methods: A review was conducted using PubMed, Google Scholar, and academic journals. Relevant keywords, including “COVID-19,” “coagulation abnormalities,” “venous thromboembolism,” “vaccine-induced thrombotic thrombocytopenia,” and “fibrinolytic,” were used. Boolean operators were applied to combine these keywords. Studies were included investigating mechanisms, risks, and therapeutic interventions for COVID-19-induced coagulopathy and vaccine-related thrombotic events. The collected studies were meticulously evaluated for relevance and quality. Results: COVID-19-induced coagulopathy results from a complex interplay of systemic inflammation, endothelial dysfunction, platelet activation, and dysregulation of the coagulation cascade, leading to a state of hypercoagulability. This hypercoagulability substantially elevates the risk of VTE, including deep vein thrombosis and pulmonary embolism. Early detection and appropriate anticoagulation therapy are crucial in mitigating these risks and preventing life-threatening outcomes. Furthermore, the review underscores rare yet severe side effects associated with specific adenoviral vector-based COVID-19 vaccines, such as VITT. Conclusion: Understanding the mechanisms behind coagulation abnormalities in COVID-19 and rare complications associated with its vaccines is vital for developing targeted therapeutic strategies. Including fibrinolytics in COVID-19, treatment protocols represents a promising approach to mitigate thrombotic events, ultimately enhancing patient outcomes and optimizing the management of this global health crisis.
Keywords: Coagulation; COVID-19; Deep Vein Thrombosis; Fibrinolytics; Pulmonary Embolism; SARS-CoV-2; Thrombolysis; Thrombosis